PD-1 and PD-L1 Checkpoint Signaling Inhibition for Cancer Immunotherapy: Mechanism, Combinations, and Clinical Outcome - Alsaab, Hashem O.; Sau, Samaresh; Alzhrani, Rami; Tatiparti, Katyayani; Bhise, Ketki; Kashaw, Sushil K.; Iyer, Arun K. (Frontiers in Pharmacology, 2017)
Several cancers are highly refractory to conventional chemotherapy. The survival of tumors in several cases is assisted by checkpoint immunomodulation to maintain the imbalance between immune surveillance and cancer cell proliferation. Check point antibody inhibitors, such as anti-PD-1/PD-L1, are a novel class of inhibitors that function as a tumor suppressing factor via modulation of immune cell-tumor cell interaction. These checkpoint blockers are rapidly becoming a highly promising cancer therapeutic approach that yields remarkable antitumor responses with limited side effects. In recent times, more than four check point antibody inhibitors have been commercialized for targeting PD-1, PDL-1, and CTLA-4. Despite the huge success and efficacy of the anti-PD therapy response, it is limited to specific types of cancers, which attributes to the insufficient and heterogeneous expression of PD-1 in the tumor microenvironment. Herein, we review the current landscape of the PD-1/PD-L1 mechanistic role in tumor immune evasion and therapeutic outcome for cancer treatment. We also review the current progress in clinical trials, combination of drug therapy with immunotherapy, safety, and future of check point inhibitors for multiple types of cancer.